THE EFFECT OF BIOPOLYMER MIXTURE AS A STABILIZATION AGENT ON PEAT SOIL TO INCREASE SOIL SHEAR STRENGTH BY DIRECT SHEAR TEST - Setyaningrum, Dewi Janti; Yuswandono, Mulyadi; Amalia, Dewi; Sihombing, Atmy Verani Rouly; Krisologus, Yulianto Petrus; Siswanto, Antonius; Sukandar, Beny Mulyana (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
Peat soil stabilization with a mixture of biopolymer materials with a mixture variation of 0.5%, 1%, 2%, 2.5%, and 3% to soil weight. This study aims to analyze the physical properties of peat soil in the Palangka Raya area and analyze the effect of adding a mixture of chitosan biopolymer with peat soil on the value of peat soil shear strength. Examination of soil physical properties includes moisture content examination, fiber content examination, specific gravity examination and volume weight examination. Meanwhile, the examination of mechanical properties in native soils and mixed soils is carried out by direct shear test. The results showed that peat soil in the Palangka Raya area had a moisture content value of 779.87%, fiber content of 61.44%, specific gravity of 1.41, and volume weight of 1.08 g/cm3. The results of direct shear testing on native soil obtained a cohesion value (c) of 0.04 kg/cm2 and a deep shear angle value (Ï†) of 4.50 °. The addition of biopolymer mixtures to the original soil results in cohesion values and deep shear angle values tend to increase with each addition of mixture variations. The highest increase in cohesion value (c), deep shear angle (Ï†) and soil shear strength (Ï„) occurred with the addition of 2.5% biopolymer and 3% biopolymer 28-day curing. This shows that the addition of biopolymer mixtures will provide an increase in the shear strength value of the soil, which makes the soil better and more stable.